ASI AND CYBERTERRORISM: NEW CHALLENGES TO INDONESIA’S NATIONAL SECURITY AND PENAL POLICY - Anakotta, Marthsian Yeksi (Fakultas Hukum Universitas Kristen Satya Wacana, 2025)
The convergence of artificial intelligence—especially artificial superintelligence (ASI)—and cyberterrorism presents serious threats to peace, order, and justice. These threats require strong criminal law enforcement and robust national security strategies. However, Indonesian criminal law policy has yet to adequately address the risks posed by ASI. Criminal law traditionally protects the interests of the state, society, and individuals—an approach also relevant to national security. Ignoring ASI’s development could lead to increased cyberterrorism, turning overlooked risks into real threats. An interdisciplinary perspective reveals that the growing intersection of AI and cyberterrorism introduces urgent new challenges for Indonesia’s national security and criminal law enforcement.